Comparative Approaches in Developing Inventory of Roles and Communication Skills for Training Needs Assessment of Frontline Extension Workers - Sukandar, Jauhari (1993)
The specific objectives of the study were to: (l) determine the appropriate approach in developing roles and communication skills required by field extension workers; (2) develop an inventory of roles of frontline extension workers using selected approaches; and (3) develop an inventory of specific communication skills needed by frontline extension workers using selected approaches. In addition, the study also attempted to develop a prototype instrument to assess the communication skills training needs of field extension workers. The study was descriptive in nature involving the use of three methods of data gathering namely open-ended questionnaire, individual interviews and focus group interview. A total of 39 respondents were selected to gather the data. The findings of the study were as follows; 23 roles of frontline extension workers were derived from the experts and practitioners through the use of open-ended questionnaire. From these 23 roles, 33 communication skills were derived. The initial 23 roles were later compressed into five major roles through the follow up interviews. Nineteen communication skills were derived from the five major roles. Through the use of focus group interview. l4 roles of extension workers were derived. The experts and practitioners listed 21 communication skills needed to perform the 14 roles of extension workers. For each of the 21 communication skills, specific skills were again derived. The study found that the focus group interview provided the most comprehensive data among the three methods of data gathering used in the study. The 21 communication skills derived through the focus group interview could be used in deter mining a prototype instrument for developing training needs assessment instrument required by frontline extension workers. Based on the findings of the study, the experience and observations of the researcher, it is recommended that focus group interview should be given priority in providing comprehensive data for developing an inventory of communication skills and roles of frontline extension workers.